Cardiac structure and function and leisure-time physical activity in the elderly: The Atherosclerosis Risk in Communities Study - Hegde, Sheila M.; Gonçalves, Alexandra; Claggett, Brian; Evenson, Kelly R.; Cheng, Susan; Shah, Amil M.; Folsom, Aaron R.; Solomon, Scott D. (European heart journal, 2016)
Adults who engage in leisure-time physical activity (LTPA) have a reduced risk of developing heart failure. We hypothesized that high levels of LTPA are associated with diminished adverse age-related changes in cardiac structure and function. We studied 4342 Atherosclerosis Risk in Communities Study participants free of cardiovascular disease who underwent standardized echocardiography. In a cross-sectional analysis, we related LTPA (poor, intermediate, or ideal) to cardiac structure and function. We also related cumulative average LTPA over 24 years and changes in LTPA categories to echocardiographic measures. Cross-sectional analysis demonstrated that ideal LTPA, compared with poor LTPA, was associated with better diastolic function [prevalence of normal diastolic function: 39.8% vs. 31.5%, P < 0.001; mean E/E' ratio (95% CI): 9.8 (9.6, 9.9) vs. 10.4 (10.2, 10.5), P = 0.001] and better systolic function [left-ventricular (LV) longitudinal strain: -18.3 (-18.4, -18.2) vs. -17.9 (-18.0, -17.8), P < 0.001] after adjusting for age, sex, race, and centre. Higher cumulative average LTPA over 24 years or an improvement in LTPA category were also, respectively, related to a more favourable E/E' ratio (P < 0.0001, P = 0.004) and longitudinal LV strain (P = 0.0002, P = 0.002). Ideal LTPA, higher average levels of LTPA over a 24-year period, and an improvement in LTPA even later in life were associated with more favourable indices of LV diastolic and systolic function in older adults. Sustaining higher levels of LTPA, and even increasing physical activity later in life, may be beneficial for older adults in attenuating expected age-related changes in cardiac structure and function.